Urgency of the Legal Structure Reformation for Law in Execution of Criminal Sanctions (Lex Scientia Law Review, 2022)
The judicial power in criminal law enforcement within the Criminal Justice System, including the execution of criminal sanctions sub-system, should be independent and self-supporting. In Indonesia, the execution of criminal sanctions sub-system is currently under the executive power that enables the practice of execution of sanctions being obstructed by many factors. In relation to that, this study explains the urgency of revision for legal structure of criminal sanctions execution and legal structure reformation for criminal enforcement in Indonesia. It employs a qualitative approach using the doctrinal research within the post-positivism paradigm. This study found that it is considered urgent or essential to reform the criminal legal structure of the national law based on philosophical, sociological, and juridical aspects abiding to Pancasila. The criminal law system covers the criminal law enforcement system which includes material criminal law sub-system, formal criminal law sub-system, and execution of criminal sanctions sub-system. Essentially, the execution of criminal sanctions sub-system acts as a sub-system of punishment. The structural reform of the systemic law in execution of criminal sanctions sub-system should be under the auspices of judicial authority, which is the Supreme Court. Therefore, this study concludes that the system should become linear, independent, synergized, and integrated with the investigative agents, prosecutors, and courts in a single criminal law system. In this way, there will be supervision and coordination in the context of the integrality of punishment, which falls under one protection of an integrated criminal law enforcement system.